Youth Hostels and Hostile Locals: Vancouver’s ‘Battle of Jericho,’ 1970 - Mahood, Linda (Urban History Review / Revue d'histoire urbaine)

(untitled) (University of Toronto Press, 2020)
Chasing tourist dollars was a necessity for many following the Second World War. However, few people in the summers of 1968 and 1969 could have escaped the sight of hundreds of fashionably penniless baby boomers hitchhiking along roads on their “annual summer trek”. Municipal authorities began to receive complaints about “scruffy young people” panhandling and sleeping rough in cities and towns along the Trans-Canada Highway. Tourism, wanted and unwanted, has the capacity to cause conflict between travelers and locals. In 1970, federally funded youth hostels became the focus of Trudeau’s Liberal government’s need to manage youth unemployment as well as radicalism on university campuses. The focus of this article is youth travel to Vancouver and Vancouverites’ responses to the National Hostel Task Force, which led to sit-ins and police-youth and youth-youth conflict, which culminated in the “Battle of Jericho”. Drawing on contemporary mainstream and university newspaper accounts, Vancouver City Police reports, RCMP intelligence files and activities at University of British Columbia, this article argues that failure to understand the diverse needs of Canada’s young people turned youth tourism into the transient youth problem in the summer of 1970.